Pengaruh Efikasi Diri Terhadap Prestasi Belajar Kognitif di SMA Katolik Don Bosco Bitung - Lintong, Marthinus Marcel; Rampengan, Angela Daniela (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2024)
This study aims to determine the effect of self-efficacy on cognitive learning achievement. This research was conducted at Don Bosco Catholic High School Bitung. The respondents in this study were X and XI-grade students. The research method used is the quantitative research method. Techniques in sampling using sampling techniques with the Slovin formula. The entire research sample totaled 130 students. The research instrument used is a questionnaire with alternative answers: Strongly Agree, Agree, Disagree, and Strongly Disagree. This study uses descriptive statistical analysis and simple linear regression analysis. The results of the study showed that Self-Efficacy had a calculated coefficient data result of 0.95 with a very good category and Cognitive Learning Achievement obtained a calculated coefficient of 0.68 with a good category. The results that have been found show that there is an effect of Self-Efficacy on Cognitive Learning Achievement at Don Bosco Bitung Catholic High School. It is said to be influential because the results obtained are the results of the coefficient of determination of 0.502. From this result by looking at the coefficient interval, it is categorized as moderate. From this explanation, it can be concluded that the effect obtained by 50% is categorized as strong and 50% is influenced by other factors, so the higher the student's self-efficacy, the more student learning achievement will increase.